Soil bacterial biodiversity is driven by long-term pasture management, poultry litter, and cattle manure inputs - Yang,Yichao; Ashworth,Amanda J.; DeBruyn,Jennifer M.; Willett,Cammy; Durso,Lisa M.; Cook,Kim; Moore, Jr.,Philip A.; Owens,Phillip R. (PeerJ, 2019)
Soil microorganisms are important for maintaining soil health, decomposing organic matter, and recycling nutrients in pasture systems. However, the impact of long-term conservation pasture management on soil microbial communities remains unclear. Therefore, soil microbiome responses to conservation pasture management is an important component of soil health, especially in the largest agricultural land-use in the US. The aim of this study was to identify soil microbiome community differences following 13-years of pasture management (hayed (no cattle), continuously grazed, rotationally grazed with a fenced, un-grazed and unfertilized buffer strip, and a control (no poultry litter or cattle manure inputs)). Since 2004, all pastures (excluding the control) received annual poultry litter at a rate of 5.6 Mg ha−1. Soil samples were collected at a 0–15 cm depth from 2016–2017 either pre or post poultry litter applications, and bacterial communities were characterized using Illumina 16S rRNA gene amplicon sequencing. Overall, pasture management influenced soil microbial community structure, and effects were different by year (P < 0.05). Soils receiving no poultry litter or cattle manure had the lowest richness (Chao). Continuously grazed systems had greater (P < 0.05) soil community richness, which corresponded with greater soil pH and nutrients. Consequently, continuously grazed systems may increase soil diversity, owing to continuous nutrient-rich manure deposition; however, this management strategy may adversely affect aboveground plant communities and water quality. These results suggest conservation pasture management (e.g., rotationally grazed systems) may not improve microbial diversity, albeit, buffer strips were reduced nutrients and bacterial movement as evident by low diversity and fertility in these areas compared to areas with manure or poultry litter inputs. Overall, animal inputs (litter or manure) increased soil microbiome diversity and may be a mechanism for improved soil health.
Keywords: Soil microbiome; Animal manure; Conservation pasture management; Microbial abundance